The economics of distributed power: A Marcellus Shale case study. (November 2017) - Yang, Yuwen; Hefley, William E.; Rajgopal, Jayant
Highlights: A small-scale distributed power system that uses natural gas is analyzed. An approach for computing overall savings in the gas/electricity supply chain is presented. Savings can be shared by the gas producer, electricity generator and electricity consumer. A case study with actual demand and cost data is presented. Abstract: We study the economics of a small natural gas powered electricity generation unit that is part of a distributed power system and is also located near a gas well, while supplying electricity to local dedicated customers. Beyond the environmental and social benefits from localizing production and usage, economic benefits accrue to (1) the gas producer, from selling close to the source and saving costs associated with gas transportation, (2) the electricity producer, from cheaper fuel and higher margins in the electricity they sell behind the meter, and (3) to the final consumer, in the form of electricity prices that are lower than the retail grid price, with little or no distribution costs. We study this arrangement using an actual distributed power generation unit along with demand and cost data from an actual potential customer, in order to estimate overall supply chain savings that could be shared between the various entities.